Endoscopic Management of Benign Airway Stenosis in Coronavirus Disease 2019 Patients - Fiorelli, Alfonso; Pecoraro, Alfonso; Failla, Giuseppe; Blasio, Francesco De; Rendina, Erino Angelo; Venuta, Federico; Andreetti, Claudio (The Thoracic and Cardiovascular Surgeon, 2023)
Background The aims of this study were to evaluate the results of endoscopic dilation for simple benign airway stenosis in coronavirus disease 2019 (COVID-19) patients and whether COVID-19 infection was associated with higher rate of recurrence compared with a control group.Methods It was an observational multicenter study including consecutive patients with simple benign airway stenosis undergoing endoscopic dilatation with at least 6 months of follow-up. The outcome of patients with COVID-19 infection was compared with that of a control group in relation to patient and stenosis characteristics, and procedure type. Then, univariable and multivariable analyses identified the risk factors for recurrence.Results Seventy-nine patients were included in the study; 56 (71%) of these developed airway stenosis after COVID-19 infection. COVID-19 patients presented a higher rate of stenosis due to prolonged intubation (82 vs. 43%; p = 0.0014); no other differences were found regarding demographic data, characteristics of stenosis, and procedure type. Twenty-four (30%) patients had recurrence after first dilatation (32% for No-COVID-19 vs. 26% for COVID-19 group; p = 0.70), and in 11 (35%) of these, the stenosis recurred after repeated endoscopic treatment (65% for No-COVID-19 vs. 45% for COVID-19 group; p = 0.40). Subglottic stenosis (p = 0.013) and the use of laser (p = 0.016) were significant predictive factors for stenosis recurrence.Conclusion COVID-19 infection did not affect the outcome of endoscopic treatment of simple airway stenosis, and the treatment of these subsets of patients should not differ from that of general population.
Keywords: benign stenosis; COVID-19 infection; rigid bronchoscopy; airway stenosis